Kualitas Produk dan Ekuitas Merek Terhadap Keputusan Pembelian Dimediasi Kepercayaan Konsumen - Alya P. Anggraini; Khansa Tahani; Thifalna Thifalna; Balqis Kanaya Alifa Ara (Pusat Riset Manajemen Dan Publikasi Ilmiah Serta Pengembangan Sumber Daya Manusia, 2023)
This study aims to determine the effect of product quality, their equity on purchasing decisions mediated by consumer trust in consumers of IPhone products in Medan City. This research uses quantitative research methods with data collection techniques using non-probability sampling. The data analysis technique used is pathanalysis or path analysis. From the research and discussion it can be concluded that product quality (X1) and brand equity (X2) applied in the city of Medan are not able to increase consumer purchasing decisions (Y). The consumer confidence factor (Z) is one of the factors that can increase consumer purchasing decisions (Y). Product quality (X1) through the mediation of consumer trust (Z) does not significantly influence consumer purchasing decisions (Y). The research model uses four (4) variables that apply the concept of mediation, where there is a relationship to the research model analyzed by Structural Equation Model - Part Least Square (SEM-PLS).